The Effectiveness of Group Counseling Services Using the Cognitive Behavior Modification (CBM) Approach in Preventing Relational Aggression in Students - Widiawati, Lika; Firman (Tafkir: Interdisciplinary Journal of Islamic Education, 2025)
Violence among adolescents is an increasingly complex phenomenon, including relational aggression, which often goes undetected due to its covert nature. Relational aggression can have serious consequences, such as depression and even suicidal tendencies among victims. This study aims to analyze the effectiveness of group counseling services using the Cognitive Behavior Modification (CBM) approach in preventing relational aggression among students at SMK 6 Padang. This study employs a quantitative research method with a quasi-experimental design in the form of a pretest-posttest control group design. The research sample consists of 12 students divided into experimental and control groups, each comprising six students, selected using a stratified random sampling technique. The research instrument utilizes a Likert scale, while data analysis is conducted using the Wilcoxon Signed Ranks Test and the Mann-Whitney Test. The findings indicate that group counseling services using the CBM approach significantly reduce relational aggression in the experimental group compared to the control group. These results affirm that the CBM approach is effective in modifying students’ thought patterns and behaviors related to relational aggression. The implications of this study provide recommendations for guidance and counseling teachers to implement CBM-based group counseling services as an intervention strategy for addressing relational aggression in the school environment.